Structural breaks and the twin deficits hypothesis : evidence from East Asian countries. - Baharumshah, Ahmad Zubaidi; Lau, Evan (Economics Bulletin, 2009)
In this paper, we examine the relevance of the twin deficits hypothesis (TDH) for selected East Asian countries. Empirical results reveal that the admission of regime shifts substantially influences the conclusion that TDH exists in four out of the seven countries that we have investigated. It seems that TDH are less likely to be evident in countries with highly developed financial systems (Singapore and Japan).